Functional polymorphisms of the arachidonic acid pathway associate with risks and clinical outcomes of allergic diseases - Sio, Yang Yie (2024)
Introduction: The arachidonic acid (AA) pathway plays a crucial role in allergic inflammatory diseases; however, the functional roles of allergy-associated single nucleotide polymorphisms (SNPs) in this pathway remain incompletely illustrated. Methods: This study belongs to a part of an ongoing Singapore/Malaysia cross-sectional genetics and epidemiological study (SMCSGES). We performed population genotyping on n = 2,880 individuals from the SMCSGES cohort to assess the associations of SNPs in the AA pathway genes with asthma and allergic rhinitis (AR). Spirometry assessments were performed to identify associations between SNPs and lung function among n = 74 pediatric asthmatic patients from the same cohort. Allergy-associated SNPs were functionally characterized using in vitro promoter luciferase assay, along with DNA methylome and transcriptome data of n = 237 peripheral blood mononuclear cell (PBMC) samples collected from a subset of the SMCSGES cohort. Results: Genetic association analysis showed 5 tag-SNPs from 4 AA pathway genes were significantly associated with asthma (rs689466 at COX2, rs35744894 at hematopoietic PGD2 synthase (HPGDS), rs11097414 at HPGDS, rs7167 at CRTH2, and rs5758 at TBXA2R, p < 0.05), whereas 3 tag-SNPs from HPGDS (rs35744894, rs11097414, and rs11097411) and 2 tag-SNPs from PTGDR (rs8019916 and rs41312470) were significantly associated with AR (p < 0.05). The asthma-associated rs689466 regulates COX2 promoter activity and associates with COX2 mRNA expression in PBMC. The allergy-associated rs1344612 was significantly associated with poorer lung function, increased risks of asthma and AR, and increased HPGDS promoter activity. The allergy-associated rs8019916 regulates PTGDR promoter activity and DNA methylation levels of cg23022053 and cg18369034 in PBMC. The asthma-associated rs7167 affects CRTH2 expression by regulating the methylation level of cg19192256 in PBMC. Conclusions: The present study identified multiple allergy-associated SNPs that modulate the transcript expressions of key genes in the AA pathway. The development of a "personalized medicine" approach with consideration of genetic influences on the AA pathway may hopefully result in efficacious strategies to manage and treat allergic diseases.